Topical application of ST266 reduces UV-induced skin damage - Guan L; Suggs A; Galan E; Lam M; Baron ED (Dove Medical Press, 2017)
Linna Guan,1 Amanda Suggs,1 Emily Galan,1 Minh Lam,1 Elma D Baron1,2 1Department of Dermatology, Case Western Reserve University, 2Cleveland Veterans Affairs Medical Center, Cleveland, OH, USA Abstract: Ultraviolet radiation (UVR) has a significant impact on human skin and is the major environmental factor for skin cancer formation. It is also believed that 80% of the signs of skin aging are attributed to UVR. UVR induces inflammatory changes in the skin via the increase in oxidative stress, DNA damage vascular permeability, and fluctuation in a myriad of cytokines. Acutely, UVR causes skin inflammation and DNA damage, which manifest as sunburn (erythema). ST266 is the secretome of proprietary amnion-derived cells that have been shown to reduce inflammation and accelerate healing of various wounds by promoting migration of keratinocytes and fibroblasts in preclinical animal studies. We hypothesized that ST266 has anti-inflammatory effects that can be used to reduce ultraviolet (UV) erythema and markers of inflammation. In this study, we examined the in vivo effects of ST266 on post UV-irradiated skin by measuring erythema, level of cyclobutane pyrimidine dimer (CPD), and expression level of xeroderma pigmentosum, complementation group A (XPA). We demonstrated that ST266 has the potential to reduce the acute effects of UV-induced skin damage when applied immediately after the initial exposure. In addition, ST266 is shown to reduce erythema, increase XPA DNA repair protein, and decrease damaged DNA. Keywords: ST266, photoaging, erythema, CPD, XPA, UV-induced DNA damage